1987
DOI: 10.1007/bf02883235
|View full text |Cite
|
Sign up to set email alerts
|

Some properties ofStreptococcus thermophilus bacteriophages

Abstract: The morphology, host range, structural proteins and serological properties of Streptococcus thermophilus phages isolated from Finnish cheese plants were investigated. The results show that all the nine phages belong morphologically to Ackermann's group B1. The host-phage reactions and plating efficiency justify the division of these phages into four specificity groups. Most of the phages showed an absolute host specificity as to their plating efficiency but were not strictly specific in the adsorption to diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…As observed for all previously characterized S. thermophilus phages, the phages used in this work belonged to the Siphoviridae family (corresponding to group B as defined by Bradley [3]) and showed a clear tendency to aggregate into clusters (6,7,12,15). These phages have double-stranded DNA genomes whose sizes range from 30.7 to 42.7 kb, in accord with previous reports (1,6,7,17,22,25).…”
Section: Discussionsupporting
confidence: 85%
“…As observed for all previously characterized S. thermophilus phages, the phages used in this work belonged to the Siphoviridae family (corresponding to group B as defined by Bradley [3]) and showed a clear tendency to aggregate into clusters (6,7,12,15). These phages have double-stranded DNA genomes whose sizes range from 30.7 to 42.7 kb, in accord with previous reports (1,6,7,17,22,25).…”
Section: Discussionsupporting
confidence: 85%
“…In a study involving nine S. salivarius subsp. thermophilus phages isolated from Finnish cheese plants, Kivi et al (1987) observed that the electrophoretic profiles of the structural proteins appeared nearly identical. The molecular masses of the four major proteins were estimated to be 63,49, 42 and 11 kDa.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, Iittle is known about phages and phage-resistance mechanisms in S salivarius subsp thermophilus. Studies based on the host range, structurai proteins, serological and morphological properties were carried out (Kivi et al, 1987). The effect of incubation temperature on the development of S salivarius subsp thermophilus and its phages was studied (Sozzi et al, 1978).…”
Section: Introductionmentioning
confidence: 99%